Prevalence of acute diarrhea and its risk factors among under five children in flood affected Dasenech District, Southern Ethiopia: a cross-sectional study - Getasew Yirdaw; Habitamu Mekonen; Bayou Tilahun Assaye; Gashaw Azanaw Amare; Chalachew Yenew (Scientific Reports)
Abstract Flooding exacerbates health challenges by spreading waterborne diseases like diarrhea through the destruction of sanitation infrastructure and contamination of drinking water sources. However, evidence on the prevalence and contributing factors of diarrheal diseases among under-five children in the Dasenech district is limited. This study aimed to assess the prevalence of acute diarrhea and its determinants among under-five children in flood-affected areas of the South Ethiopia region. A community-based cross-sectional study was conducted from July 1 to July 15, 2024, in flood-affected areas of the Dasenech district, involving 696 under-five children. Five kebeles were purposively selected, followed by the proportional allocation of households, after which a systematic sampling technique was applied to identify study participants. Data were collected using a pretested and structured questionnaire administered by trained interviewers. Multivariable logistic regression analysis was performed to identify factors associated with acute diarrhea, with statistical significance set at p < 0.05 and a 95% confidence interval (CI). The prevalence of acute diarrhea was 31.6% (95% CI: 28.7–34.3%). Significant predictors of acute diarrhea included non-adherence to exclusive breastfeeding (AOR: 2.14, 95% CI: 1.65–3.98), lack of latrines (AOR: 12.08, 95% CI: 9.77–13.13), unsafe disposal of child excreta (AOR: 3.86, 95% CI: 2.38–6.26), home delivery (AOR: 6.02, 95% CI: 5.53–8.82), and a recent history of diarrhea among mothers or caregivers (AOR: 3.14, 95% CI: 1.33–5.66). Acute diarrhea is highly prevalent among under-five children in the Dasenech district. The findings underscore the need for targeted public health measures, such as improving waste management, promoting exclusive breastfeeding, constructing and utilizing latrines, and addressing maternal and caregiver health, to mitigate the burden of diarrheal diseases in this vulnerable population.